2017
DOI: 10.1139/bcb-2016-0144
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of latex from Hevea brasiliensis (clone RRIM 600)

Abstract: The natural rubber latex extracted from the bark of Hevea brasiliensis plays various important roles in today's modern society. Following ultracentrifugation, the latex can be separated into 3 layers: C-serum, lutoids, and rubber particles. Previous studies have shown that a large number of proteins are present in these 3 layers. However, a complete proteome for this important plant is still unavailable. Protein sequences have been recently translated from the completed draft genome database of H. brasiliensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…It is known that rubber latex contains many macromolecular substances, such as proteins, sugars and alkaloids, and the NRB is a complex process [ 7 , 44 ]. Many proteins involved in the NRB process have been identified by proteomics-based technologies from different latex components [ 2 , 7 , 8 , 10 , 11 , 12 , 13 , 15 , 16 , 45 ]. These proteomics results revealed that rubber latex has a high protein content, and different kinds of PTMs have been determined in rubber latex to efficiently regulate NRB [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that rubber latex contains many macromolecular substances, such as proteins, sugars and alkaloids, and the NRB is a complex process [ 7 , 44 ]. Many proteins involved in the NRB process have been identified by proteomics-based technologies from different latex components [ 2 , 7 , 8 , 10 , 11 , 12 , 13 , 15 , 16 , 45 ]. These proteomics results revealed that rubber latex has a high protein content, and different kinds of PTMs have been determined in rubber latex to efficiently regulate NRB [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycerate mutase is known to exert a certain physiological impact in plant cells. It was identified as a metabolic protein from lettuce latex sap [ 47 ], rubber latex [ 13 ] and the washed solutions from rubber particles [ 48 ]. In this proteomics study, we found it was glycosylated (spot 3) in the 2-DE gels ( Figure 2 ) and increased by 2.3-fold after ethylene stimulation for three days ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many proteins had been identified by proteomics-based technologies from different Hevea latex components, such as total latex ( D’Amato et al, 2010 ; Li et al, 2011 ; Wang et al, 2015 ; Dai et al, 2016 ; Habib et al, 2017 ), rubber particles ( Rojruthai et al, 2010 ; Xiang et al, 2012 ; Dai et al, 2013 , 2016 ; Wang et al, 2016 ; Yamashita et al, 2016 ), C-serum ( Wagner et al, 2007 ; Wang et al, 2010 ; Havanapan et al, 2016 ), and lutoids ( Wang et al, 2010 , 2013 ; Habib et al, 2017 ). Proteins involved in mevalonate (MVA) pathway are crucial for NRB ( Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…All liquid chromatography-mass spectrometry (LC-MS) and tandem mass spectrometry (MS/MS) analyses were carried out according to our previous work (Habib et al 2016) by using Thermo LTQ/Orbitrap Velos coupled with Easy-nLC II system. Briefly, the tryptic-digested peptides chromatographic separation was performed using Easy-Column C18-A2 (100 0.75 mm i.d., 3 m) coupled with pre-column (Easy-Column, 20 0.1 mm i.d., 5 m) at flow rate of 0.3 l/min and injection volume of sample was 10 µl.…”
Section: Liquid Chromatography Mass Spectrometrymentioning
confidence: 99%